Implementasi Penggunaan Anggaran di Kecamatan Sidoarjo, Kabupaten Sidoarjo, Provinsi Jawa Timur - Athaya, M. Daffa Amru Prima; Sinatra, Willdan; Utomo, Decky Dwi; Ardieansyah, Ardieansyah (Innovative: Journal Of Social Science Research, 2025)
This study examines the implementation of budget utilization in Sidoarjo Sub-district, Sidoarjo Regency, East Java Province. The primary focus is on how the budget is realized to support public service programs and activities, as well as the reporting and accountability mechanisms carried out by sub-district officials. Based on observations during the internship, it was found that although the planning and execution processes followed the official planning documents, challenges remain in the reporting stage— particularly related to administrative delays and limited human resource capacity in using accounting systems. This study highlights the importance of strengthening technical capacity and accountable financial governance at the sub-district level to achieve efficiency and effectiveness in regional financial management.